Financial planning and counseling scales - Grable, John E.; Archuleta, Kristy L.; Nazarinia, R. Roudi (Springer eBooks., 2011)
A salient trend during the current economic crisis is the increasing number of consumers paying closer attention to their spending and saving habits in efforts to control their finances. Not surprisingly, these same uncertain times are witnessing the growth not only of financial planning services, but of financial counseling and therapy. Accompanying the move toward professional standards and an academic research base is the need for a reliable source of quality assessment tools for use with clients, for research, and for training. Financial Planning and Counseling Scales admirably fills this need by collecting a diverse range of instruments specifically designed for the financial fields. The majority of the scales here have never been published in any other manuals or handbooks, appearing only in peer-reviewed journals or, in some cases, dissertations. This timely volume: Reproduces over 280 scales useful across a variety of circumstances, Provides key details for each scale, including source, purpose, test sample, scoring information, and discussion of reliability and validity, Clearly defines financial counseling/therapy as a field of study and practice (particularly in the context of marriage and family therapy) and establishes the role of psychometric assessment, Summarizes a range of theoretical models (e.g., cognitive-behavioral, solution-focused, systems) for financial therapy, Offers guidelines for evaluating scales, and for constructing original instruments. Financial Planning and Counseling Scales is a first-of-its-kind resource for researchers, educators, and practitioners in family and consumer economics, personal finance, household finance, and financial therapy as these domains evolve.